Virtual Reality Impacts on Novice Programmers' Self-Efficacy - Sun, Nanlin; Lages, Wallace S. (IEEE transactions on visualization and computer graphics, 2025)
Virtual Reality has been used to improve motivation and help in the visualization of complex computing topics. However, few studies directly compared immersive and non-immersive environments. To address this limitation, we developed Abacus, a programming environment that can run in both immersive and non-immersive modes. We conducted a between-subjects study (n=40), with twenty participants assigned to the desktop mode and twenty participants assigned to the VR mode. Participants used a block-based editor to complete two programming tasks: a non-spatial procedural task, and a spatial 3D math task. We found that VR led to higher gains in self-efficacy and that the gain was significant for participants with lower initial levels of experience and spatial skills.